Pengaruh Profitabilitas, Likuiditas, Dan Leverage Terhadap Kebijakan Dividen Kas (Studi Pada Perusahaan Real Estate Dan Properti Yang Terdaftar Di Bursa Efek Indonesia Periode 2013-2015) - Putra, Harrys Amdana Andika; Made, Anwar; Dianawati, Eris (Jurnal Riset Mahasiswa Akuntansi, 2018)
This study aims to determine how much influence the profitability, liquidity, and leverage of cash dividend policy. This research uses descriptive quantitative data types and secondary data sources. The sample of this research were 49 real estate and property companies using a sampling technique with purposive sampling. Data collection techniques from the internet, journals, books, articles, and previous thesis. The variables used are independent variables including profitability using the formula of NPM, ROI, and ROE ratio, liquidity using the formula of QR and CR ratio, and leverage using the DAR and DER ratio formula. Whereas the cash dividend policy uses the cash dividend formula divided by the number of company shares. The data analysis technique used is multiple linear regression. The results of this study indicate that the profitability which is posited by return on investment (ROI), and leverage which is predicted to be a debt to asset ratio (DAR) and debt to equity ratio (DER) partially have no significant effect on cash dividend policy. However, profitability proxied by net profit margin (NPM) and return on equity (ROE), liquidity which is proxied by current ratio (CR) and quick ratio (QR) has a significant positive effect on cash dividend policy. While simultaneously NPM, ROI, ROE, CR, QR, DAR, and DER significantly influence cash dividend policy.